The Complexity of the cGAS-STING Pathway in CNS Pathologies - Fryer, Amelia L.; Abdullah, Amar; Taylor, Juliet M.; Crack, Peter J. (Frontiers in Neuroscience, 2021)
Neuroinflammation driven by type-I interferons in the CNS is well established to exacerbate the progression of many CNS pathologies both acute and chronic. The role of adaptor protein Stimulator of Interferon Genes (STING) is increasingly appreciated to instigate type-I IFN mediated neuroinflammation. As an upstream regulator of type-I IFNs, STING modulation presents a novel therapeutic opportunity to mediate inflammation in the CNS. This review will detail the current knowledge of protective and detrimental STING activity in acute and chronic CNS pathologies and the current therapeutic avenues being explored.